Արցախի բնական հուշարձանները և դրանց պաշտպանության խնդիրները - Գագինյան, Ռ. Խ.; Առաքելյան, Յու. Ա.; Գևորգյան, Ֆ. Ս․
Уникальные природные памятники Арцаха имеют Большое научное, историческое, краеведческое, познавательное, эстетическое и практическое значение. Природные памятники Арцаха можно разделить на 4 группы: 1. Ландшафтно-пейзажные долины рек Тертера, Трхи, каньон Унута, многочисленные уникальные скалы, оврывы, водопады, пороги, нерукотворные скальные скульптуры, отдельные участки лесного ландшафта. 2. Научно-познавательные отдельные геологические овножения, геологические тела и формы рельефа (оползни, ведленды, некки, воклюзные источники), реликтовые растения (каркас, рододендрон и т. д.), вековые и священные деревья. 3. Историко-археологические-карстовые пещеры, неприступные скалы, над которыми построены крепости. 4., Наконец, природные памятники также имеют практическое значение для развития туризма и отдыха населения. До последнего времени охране природных памятников в Арцахе не уделялось внимания. Для организации охранных равот необходимо изучение, учет и паспортизация всех природных памятников. Необходимо взять под охрану отдельные реликтовые, исчезающие растения, вековые деревья, а также некоторые отдельные уникальные памятники, установить заповедный режим в долинах рек Тертер, Трхи, в каньоне Унут. Unique Artsakh natural view-worthy sites have a great scientific, historical, cognitive, aesthetic and practical impact. Artsakh natural view-worthy sites can be classified into 4 groups: 1) picturesque landscape sites - such as valleys of the Terter and Trghee rivers, the canyon Unoot, a great number of unique rocks, precipices, waterfalls, rapids, sculpture created by natural forces, certain parts of the wooded landscape; 2) scientific cognitive sites - certain escarpments, geological bodies and relief forms (landslides, bad lands, necks, springheads), relic vegetation (Ulmus, rhododendrons and others), centuries-old and sacred trees; 3) historio-archeologic sites - karst caves, unclimbable cliffs having been used as basements for citadels; 4) natural view-worthy sites’ having practical value for development of tourism and recreation of population. T ill recently Artsakh natural view-worthy sites protection was not considered of any importance. In the franiework of protection efforts it is the must to study, register and organize certification of all the Artsakh natural •viewrworthy sites. A number of relic, disappearing plants should be taken under protection as well as centuries-old tress and some other Artsakh natural view-worthy sites. The Terter and Trghee rivers valleys together with the canyon Unoot should be made reserves.
Keywords: Աշխարհագրություն